Changes of Serum Adiponectin and Glycated Albumin Levels in Gestational Diabetes Mellitus Patients and Their Relationship with Insulin Resistance - Qingju WANG; Juan DU; Fenglian LIU (Tehran University of Medical Sciences, 2020)
Background: We aimed to investigate the changes of serum adiponectin and glycated albumin (GA) levels in gestational diabetes mellitus patients and their relationship with insulin resistance. Methods: Overall, 137 pregnant women were enrolled from Jinan City People's Hospital, Laiwu District, China from Jan 2015 to Jun 2018. Among them, 71 pregnant women with gestational diabetes mellitus were examined as diabetes group, and 66 normal pregnant women as normal pregnant women group. In addition, 58 normal non-pregnant women of childbearing age who were examined in our hospital during the same period were selected as a control group. The serum adiponectin and GA levels of the three groups were compared, and the relationship between serum adiponectin, GA levels and insulin resistance was analyzed. Results: The serum adiponectin level of pregnant women in gestational diabetes mellitus (GDM) group was significantly lower than that of normal pregnant women and control group (P=0.031, P=0.027). The serum GA level of pregnant women in GDM group was significantly higher than that of normal pregnant women and control group (P<0.001). Pearson correlation analysis showed that GA was positively correlated with Fasting plasma glucose (FPG), Fasting insulin (FINS) and Insulin resistance index(HOMA-IR) levels (P<0.001), while adiponectin was negatively correlated with FPG FINS and HOMA-IR levels (P<0.001). Conclusion: Abnormal levels of serum GA and adiponectin are closely related to insulin resistance in patients with gestational diabetes mellitus. Detection of serum GA and adiponectin levels can diagnose gestational diabetes mellitus quickly and effectively.